Evaluating PVTs diagnostic accuracy through simulation study in Indonesian older adults - Yanuar, Alfo; Adhiatma, Widhi; Hendriks, Marc P. H.; Halim, Magdalena Surjaningsih (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: The accurate assessment of cognitive ability requires valid data, particularly among older adults. Non-credible performance, or symptom exaggeration, threatens the validity of neuropsychological assessments in Indonesia. Purpose: This study aims to examine the diagnostic accuracy of four Performance Validity Tests (PVTs) by comparing healthy older adults and individuals simulating cognitive impairment. Method: An experimental two-group design was used (N=25). Participants passed rigorous cognitive screening (MoCA > 26) and were randomly assigned to a control (n=12) or experimental (n=13) group. PVTs included NV-MSVT, TMJPI, CIHT, and embedded TMT measures. Findings: Mann-Whitney U tests showed significant differences (p< .05) between groups, with controls outperforming simulators. ROC analysis yielded optimal cut-off scores for all PVTs: NV-MSVT A1 (≤ 83), NV-MSVT A2 (≤ 79), TMJPI (≤ 87), CIHT (≤ 9), TMT-A (≥ 131), and TMT-B (≥ 200). AUC values ranged from .713 to .907, indicating good to excellent accuracy in distinguishing the groups. Implication: These findings establish a robust empirical foundation for more ethical and valid neuropsychological research in Indonesia, providing culturally relevant cut-offs to mitigate misdiagnosis in clinical practice, advance cross-cultural neuropsychology in Asia, and strengthen administrative and forensic decision-making.